Counteracting Alzheimer's disease via normalizing neurovascular unit with a self-regulated multi-functional nano-modulator - Xue Xia; Ya Wei; Qianqian Huang; Yang Zhou; Xiaorong Wang; Yulong Shi; Xiaotong Yang; Wenqin Yang; Yiwei Zhang; Ting Lei; Yuan Huang; Hanmei Li; et al. (Acta Pharmaceutica Sinica B)
The neurovascular unit (NVU) is highly responsible for cerebral homeostasis and its dysfunction emerges as a critical contributor to Alzheimer's disease (AD) pathology. Hence, rescuing NVU dysfunction might be a viable approach to AD treatments. Here, we fabricated a self-regulated muti-functional nano-modulator (siR/PIO@RP) that can intelligently navigate to damaged blood-brain barrier and release therapeutical cargoes for synergetic AD therapy. The resulting siR/PIO@RP enables self-regulation of its distribution in accordance with the physio/pathological state (low/high RAGE expression) of the target site via a feedback loop. siR/PIO@RP is capable of performing intricate tasks and goes beyond the capabilities of single-target therapeutic agents utilized in AD therapy, such as reducing cerebral Aβ load, relieving neuroinflammation, and alleviating the dysfunction of NVU. Overall, the current study provides proof of concept that normalizing NVU holds promise as a means of alleviating AD symptoms.